Clinical analysis of hyperbaric oxygen combined with subdural drilling and drainage in the management of subdural effusion type IV with intracranial infection in infant patients - Chen, Liuyin; Yue, Yanke; Luo, Pengyuan; Qu, Yi; Fang, Jiangshun; Xin, Chaojun; Lv, Lige; Luan, Jimei; Cheng, Zhenghai; Yang, Zhiguo; Sun, Yaning (Frontiers in Neurology, 2024)
Background To explore the therapeutic effect of hyperbaric oxygen combined with subdural drilling and drainage (SDD) on subdural effusion type IV with intracranial infection in infant patients. Methods This retrospective controlled study included 328 infant patients with subdural effusion type 4 with intracranial infection between January 2005 and January 2023. 178 patients were treated by hyperbaric oxygen combined with SDD (group A). 142 cases were treated with SDD (group B). 97 infants were only received hyperbaric oxygen (group C). Clinical outcomes, the control time of intracranial infection, complications, and the degree of brain re-expansion after 6 months of treatment were compared among the three groups. According to the comprehensive evaluation of treatment effectiveness and imaging results, it is divided into four levels: cured, significantly effective, improved, and ineffective. Results No patient died during follow-up. The three groups were similar regarding age, sex, the general information, and clinical symptoms (p > 0.05). All intracranial infections in the children were effectively controlled. There was no difference in infection control time between group A and group B, and there was no statistical significance. However, the control time of intracranial infection between the two groups was different from that of group C, which was statistically significant. Compared with group B and group C, the degree of brain re-expansion in group A has obvious advantages and significant differences. The effective rates of the three groups were 83.7%, 58.5%, and 56.7%, respectively. There were 28 cases of subcutaneous hydrops in group A and 22 cases of subcutaneous hydrops in group B after operation, and no other serious complications. Conclusion The SDD is safe and effective for infant patients with intracranial infections through fluid replacement and intrathecal antibacterial. Hyperbaric oxygen is effective as an adjuvant therapy to promote brain re-expansion.